The Chibok girls: the Boko Haram kidnappings and Islamist militancy in Nigeria - Habila, Helon (Columbia Global Reports, 2016)
"Acclaimed novelist Helon Habila, who grew up in northern Nigeria, returned to Chibok and gained intimate access to the families of the kidnapped to offer a devastating account of a tragedy that stunned the world. With compassion and a deep understanding of the historical context, Habila tells the stories of the girls and the anguish of their parents; chronicles the rise of Boko Haram and the Nigerian government's inept response; and captures the indifference of the media and the international community whose attention has long moved on. Employing a fiction writer's sensibility and a journalist's curiosity, The Chibok Girls provides poignant portraits of everyday Nigerians whose lives have been transformed by extremist forces. Habila illuminates the long history of colonialism--and unmasks cultural and religious dynamics--that gave rise to the conflicts that have ravaged the region to this day." -- Publisher's description